Respon Pertumbuhan dan Hasil Tanaman Kailan (Brassica oleraceae) Terhadap Penggunaan Kombinasi Pupuk Kotoran Kambing dan Pupuk NPK 16-16-16 - Taofik, Ahmad (Universitas Batanghari, 2024)
Kailan (Brassica oleraceae) is a vegetable with thick, dark green leaves and crunchy stems, often used in Asian cooking. This plant is adaptable to a variety of growing conditions, making it suitable for the home gardening, and it is relatively easy to cultivate with the ability to grow in a various of climates. Most farmers still rely on synthetic fertilizers in kailan cultivation. Using organic fertilizer can improve soil health and reduce the risk of accumulation of dangerous chemicals in the food. The research aims to study the substitution of synthetic NPK fertilizer with goat manure. The experiment is the method used, consisting of 6 treatments and repeated 5 times. The treatments consisted of A: Control (no fertilizer), B: 100% dose of goat manure, C: 75% dose of goat manure + 25% dose of NPK fertilizer, D: 50% dose of goat manure + 50% dose of fertilizer NPK, E: 25% dose of goat manure + 75% dose of NPK fertilizer, F: 100% dose of NPK fertilizer. The research variables consisted of soil analysis, goat manure analysis, plant height, number of leaves, leaf area, plant fresh weight, plant dry weight, and shoot root ratio. The data obtained were analyzed of variance using data analysis data processing in the Excel program, if they were significantly different, continued with Duncan's multiple range test. Based on the results obtained, it was concluded that goat manure could be used as a substitute for synthetic fertilizer